2013
DOI: 10.1159/000356609
|View full text |Cite
|
Sign up to set email alerts
|

Osthole Exhibits Anti-Cancer Property in Rat Glioma Cells Through Inhibiting PI3K/Akt and MAPK Signaling Pathways

Abstract: Aims: The purpose of this study was to investigate how Osthole affects glioma cell proliferation, apoptosis, invasion and migration. Methods: Rat glioma cells were treated with different concentrations of Osthole (0 µM, 25 µM, 50 µM, and 100 µM). Cell proliferation was assessed by measuring PCNA expression and CCK8 assay at different time points. Apoptosis was evaluated by measuring the expression of pro-apoptotic protein including Bax, Bcl2, PARP, and cleaved Caspase3, and of anti-apoptotic protein Survivin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…Researchers try to enhance anti-lung cancer activity of curcumin via catanionic lipid nanosystems [8]. Several reports have demonstrated that osthole inhibited cell growth and proliferation by inducing apoptosis, cell cycle arrest, and inhibition of migration and invasion in various types of tumors, such as glioma, colorectal cancer, and lung cancer [14,30,31,32]. Our experiment demonstrated that osthole inhibits MG-63 and SAOS-2 cells growth by at least partially inducing cell cycle arrest and inhibition of migration and invasion, suggesting that osthole could be used for the treatment of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers try to enhance anti-lung cancer activity of curcumin via catanionic lipid nanosystems [8]. Several reports have demonstrated that osthole inhibited cell growth and proliferation by inducing apoptosis, cell cycle arrest, and inhibition of migration and invasion in various types of tumors, such as glioma, colorectal cancer, and lung cancer [14,30,31,32]. Our experiment demonstrated that osthole inhibits MG-63 and SAOS-2 cells growth by at least partially inducing cell cycle arrest and inhibition of migration and invasion, suggesting that osthole could be used for the treatment of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that Akt, p38, JNK, and ERK1/2 cascades have critical roles in the induction of apoptosis [30,31]. Therefore, to elucidate the mechanisms underlying IUA-induced apoptosis, the levels of Akt, p-Akt, p38, p-p38, JNK, p-JNK, ERK1/2, and p-ERK1/2 were analyzed by Western blotting in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied MAPKs are the p38 MAPK, extracellular signal-regulated protein kinases 1/2 (ERK1/2) and c-Jun N-terminal kinases (JNK) (6). It has been reported that p38 MAPK and ERK1/2 pathways are important for glioma development (10)(11)(12). Previous studies have demonstrated that MAPKs (p38 MAPK and ERK1/2) also activate other signaling cascades, such as cyclooxygenase-2 (COX-2) (13,14), in a variety of cancer cell types.…”
Section: Introductionmentioning
confidence: 99%